1999
DOI: 10.1086/302567
|View full text |Cite
|
Sign up to set email alerts
|

A Genomewide Screen for Schizophrenia Genes in an Isolated Finnish Subpopulation, Suggesting Multiple Susceptibility Loci

Abstract: Schizophrenia is a severe mental disorder affecting approximately 1% of the world's population. Here, we report the results from a three-stage genomewide screen performed in a study sample from an internal isolate of Finland. An effort was made to identify genes predisposing for schizophrenia that are potentially enriched in this isolate, which has an exceptionally high lifetime risk for this trait. Ancestors of the local families with schizophrenia were traced back to the foundation of the population in the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
209
2
4

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(222 citation statements)
references
References 40 publications
7
209
2
4
Order By: Relevance
“…48 Schizophrenia susceptibility genes have been proposed on many chromosomes including 1q, 5q, 6p, 6q, 8p, 10p, 13q, 18p and 22q (reviewed in O'Donovan et al 11 ). PLXNA2 is located in the 1q32 region, a schizophrenia locus that was originally identified in a family-based linkage study 16 and has received support from several independent studies. [18][19][20] However, there have been several studies that did not confirm this locus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…48 Schizophrenia susceptibility genes have been proposed on many chromosomes including 1q, 5q, 6p, 6q, 8p, 10p, 13q, 18p and 22q (reviewed in O'Donovan et al 11 ). PLXNA2 is located in the 1q32 region, a schizophrenia locus that was originally identified in a family-based linkage study 16 and has received support from several independent studies. [18][19][20] However, there have been several studies that did not confirm this locus.…”
Section: Discussionmentioning
confidence: 99%
“…PLXNA2 is located approximately 35 kb upstream of D1S2891, a marker for which Hovatta et al 16 have observed a maximum pairwise LOD score of 3.82 in a linkage study for schizophrenia. In a subsequent fine-mapping project, the same group identified a marker (D1S245) with an LOD score of 2.3 that lies within 1 Mb of the PLXNA2 gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of Finnish twins used microsatellite markers that had previously been shown to form a schizophrenia linked allelic haplotype spanning 1q32.2-q41. 23 The most telomeric of these markers (ie those immediately proximal to TRAX/DISC) displayed the strongest linkage and association to quantitative measures of visuospatial working memory and visual attention. 24 Also, a family-based, genome-wide scan using a number of quantitative traits of cognitive functions observed some evidence of linkage (lod41.5) to verbal memory functions at the 1q41 locus 25 ( Figure 1).…”
mentioning
confidence: 99%
“…1 There is substantial evidence supporting the genetic etiology of schizophrenia in a number of systematic linkage scans. To date, some schizophrenia susceptibility loci, one of which is 1q21-22, [2][3][4][5] close to the location of the MPZL1/PZR gene have been reported. MPZL1 (myelin protein zero like 1), a 43-kDa hyperphosphorylated transmembrane glycoprotein mapped to 1q23.3, was identified by Zhao and Zhao.…”
Section: Introductionmentioning
confidence: 99%